PENGARUH CURRENT RATIO, TOTAL ASSET TURNOVER, DEBT TO EQUITY RATIO, DAN WORKING CAPITAL TURNOVER TERHADAP RETURN SAHAM DENGAN RETURN ON ASSET SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN LQ45 - Hasbullah Hasbullah; Mohammad adam; umar hamdan (JEMBATAN, 2017)
This research aimed to analyze the effect of variable Current Ratio (CR), TotalAsset Turnover (TAT), Debt Equity Ratio (DER), and Working Capital Turnover(WCT) with stock return, put the test and analyze is Return on Asset (ROA) moderateeffect on relations Current Ratio (CR), Total Asset Turnover (TAT), Debt Equity Ratio(DER), and Working Capital Turnover (WCT) with Stock return in Company LQ45.Population in this research as much 45 Company with 5 selected as sample of theresearch during period 2009-2015 with multi-shapes sampling in a purposive. The datais analyzed using multiple regression analysis and moderated regression anlysis. Theresult of this research proving that : CR, TAT, DER, and WCT have no effect on stockreturn, Return on Asset (ROA) have moderate Current Ratio (CR) on stock return, butReturn on Asset (ROA) have no moderate Total Asset Turnover (TAT), Debt EquityRatio (DER), and Working Capital Turnover (WCT) with stock return.Keywords : Fundamental Ratio, Return on Asset, Stock Return